(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article deals with the essence and the importance of analytical evaluation of financial results of enterprises. The attention is focused on the changes of regulated national situation (standard) accounting 1 «General Requirements for Financial Statements», which occurred in the structure of the income statement (statement of comprehensive income). When covering scientific approaches to the analysis of financial results and planned analysis of the sequence of the research object. The expediency of profit analysis in conjunction with the assessment of the cash flows of the company and refined method of calculating margins.